Phage display-based identification and potential diagnostic application of novel antigens from Mycoplasma mycoides subsp. mycoides small colony type - Naseem, S.; Meens, J.; Jores, Joerg; Heller, M.; Dabel, S.; Hust, M.; Gerlach, G.F. (Elsevier, 2010)
Contagious Bovine Pleuropneumonia caused by Mycoplasma mycoides subsp. mycoides small colony type is a respiratory disease of considerable economic importance in sub-Saharan Africa; control of the disease in Africa is hampered by diagnostic tests which are suited for herd-level but not for individual animal diagnostics. In the work presented we identified 22 potential immunogenic antigens of the Kenyan outbreak strain B237 by using phage display technology. We determined the relative strength of immunogenicity, the discriminatory capacity between bovine positive and negative sera, and the cross-reactivity with rabbit hyperimmune sera directed against 15 different mycoplasmal species. The three best-performing antigens, a conserved hypothetical protein (MSC_0636), a glycosyl transferase (MSC_0108), and an acyl carrier protein phosphodiesterase (MSC_0029) were considered candidate diagnostic proteins. They were expressed as GST-fusion proteins in Escherichia coli, purified, and used in an ELISA as solid phase antigens. The diagnostic potential of the recombinant antigens was tested using the sera of ten experimentally infected animals and six control animals. This prototype test resulted in 100% diagnostic sensitivity and specificity. In comparison, the complement fixation test and the competitive ELISA performed with a diagnostic sensitivity of 70% and 60%, respectively.